Role Medium-Chain Fatty Acids in the Lipid Metabolism of Infants - Yuan, Tinglan; Wang, Lei; Jin, Jun; Mi, Lijuan; Pang, Jinzhu; Liu, Zhengdong; Gong, Jinyan; Sun, Cong; Li, Jufang; Wei, Wei; Jin, Qingzhe; Wang, Xingguo (Frontiers in Nutrition, 2022)
Human breastmilk, the ideal food for healthy infants, naturally contains a high concentration of medium-chain fatty acids (MCFAs, about 15% of total fatty acids). MCFAs are an important energy source for infants due to their unique digestive and metabolic properties. MCFA-enriched oils are widely used in infant formula, especially the formula produced for preterm infants. Recently, there has been a growing interest in the triglyceride structure of MCFAs in human milk, their metabolism, and their effects on infant health. This study summarised the MCFA composition and structure in both human milk and infant formula. Recent studies on the nutritional effects of MCFAs on infant gut microbiota have been reviewed. Special attention was given to the MCFAs digestion and metabolism in the infant. This paper aims to provide insights into the optimization of formulations to fulfil infant nutritional requirements.